2019
DOI: 10.1073/pnas.1901247116
|View full text |Cite
|
Sign up to set email alerts
|

Rapid experimental evolution of reproductive isolation from a single natural population

Abstract: Ecological speciation occurs when local adaptation generates reproductive isolation as a by-product of natural selection. Although ecological speciation is a fundamental source of diversification, the mechanistic link between natural selection and reproductive isolation remains poorly understood, especially in natural populations. Here, we show that experimental evolution of parasite body size over 4 y (approximately 60 generations) leads to reproductive isolation in natural populations of feather lice on bird… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 77 publications
1
42
0
2
Order By: Relevance
“…This variation makes it possible to transfer C. columbae among diverse size and color phenotypes within the single native host species. Recently, we showed that switching lice to pigeons of different sizes and colors elicits rapid population-level changes in louse size and color ( Bush et al 2019 ; Villa et al 2019 ). Despite the wealth of phenotypic data about real-time adaptation of C. columbae to changes in host environment, the underlying molecular mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This variation makes it possible to transfer C. columbae among diverse size and color phenotypes within the single native host species. Recently, we showed that switching lice to pigeons of different sizes and colors elicits rapid population-level changes in louse size and color ( Bush et al 2019 ; Villa et al 2019 ). Despite the wealth of phenotypic data about real-time adaptation of C. columbae to changes in host environment, the underlying molecular mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal is to design and synthesize a new Mimulus species (sensu Duffy et al, 2007;Villa et al, 2019), pollinated by hawkmoths and reproductively isolated from its red-flowered, hummingbird-pollinated ancestor, M. cardinalis. Several traits already present in Mimulus, including nocturnal anthesis, large nectar volume in M. cardinalis, and floral scent, suggest that the evolution of hawkmoth pollination in section Erythranthe should be genetically tractable and require few mutational changes.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research has shown this to occur in wing lice from pigeons; lice transferred to different-sized pigeons were often unable to avoid preening behavior and were quickly removed by the host (Bush & Clayton, 2007;. This can lead to reproductive isolation between populations of lice and ultimately to speciation (Villa et al, 2019). However, host body size is likely not a crucial factor for grouse and their lice.…”
Section: Factors Influencing the Relationships Between Grouse And Tmentioning
confidence: 99%